Biocontrol Agents and Organic Matters for Meloidogyne incognita Infection of Beta vulgaris L.: Impact of Meloidogyne incognita on beetroot and spinach cultivars (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Currently, the utilization of M. incognita-resistant cultivars is regarded as a nematodemanagement strategy that is both economically feasible and ecologically benign, with no discerniblerisks to human health. The primary aim of the investigation was to assess the effects of screening forroot-knot nematodes, specifically Meloidogyne incognita, on the development, biochemistry, andpathology of beetroot and spinach cultivars. The research investigations detailed in the dissertationwere carried out both in vitro and in vivo within the Department of Botany at Aligarh Muslim University,located in Aligarh (U.P.). The present study selected Beta vulgaris L. Cv. Ruby Queen and Spinach(Spinacea oleracea L. cv. All Green) as experimental plants, belonging to the Amaranthaceae family. Thestatistical analysis of the trials was performed utilizing the one-way analysis of variance (ANOVA)method and the R statistical software. The results indicate that the effects of M. incognita on variousplant growth parameters (e.g. shoot and root length, shoot and root fresh weight, and number of leavesper plant), biochemical parameters (e.g. total chlorophyll and carotenoid contents), and pathologicalparameters (e.g. number of eggmasses per root, number of eggs per eggmass, nematode population per250 gm soil, and root-knot index) were not consistent across all cultivars that were analysed.